Synthesis and Characterization of Carboxymethylated Locust Bean Gum for Developing Compression Coated Mucoadhesive Tablets of Cinnarizine - Giri, Pankaj; Singh, Inderbir (Asian Journal of Chemistry, 2021)
Carboxymethylated locust bean gum (CLBG) was synthesized by carboxymethylation of locust bean gum (LBG) using monochloroacetic acid followed by characterization involving SEM, XRD and FTIR techniques. The CLBG exhibited changes in the surface morphology along with relative amorphous nature as indicated in SEM and XRD analysis, respectively. In SEM images, locust bean gum (LBG) exhibited irregular particle with smooth surface morphologies whereas CLBG depicted surface roughness with relatively irregular edges. XRD study indicated relative amorphous nature of CLBG. The modified gum was employed for developing compression coated tablets of cinnarizine. The core tablets coated with CLBG exhibited mucoadhesive detachment force of 11.44 ± 2.09 to 16.07 ± 1.88 N compared to 4.10 ± 0.95 to 5.52 ± 1.13 N of locust bean gum coated tablets. The CLBG depicted better sustained drug release behaviour when compared with the pure gum. In conclusion CLBG is a suitable polymer candidate for developing mucoadhesive drug delivery systems with controlled release property.